Understanding the image of Indonesia in UK consumer : an analysis of Visit Indonesia 2008 campaign - Gitadharmesti, Astri (2008)
Tourist destinations have been facing an intensified competition among each other. Each destination feels the crucial need to differentiate themselves by trying to highlight their uniqueness through marketing effort. Destination branding came up as a concept that is believed could enable destinations to succeed. Nevertheless, the difficult process to build a strong and distinct destination brand have been widely acknowledged. This study has tried to observe how Indonesia's branding initiative effectively build awareness about the positive image of Indonesia and build a positive attitude among the UK working population. The study especially focus on Indonesia's latest national tourism campaign called 'Visit Indonesia 2008'.